Optimal dipole planar antenna array design for different UHF band applications using cuckoo search algorithm. Issue 2 (2016) - Pradhan, Hrudananda; Mangaraj, Biswa Binayak; Misra, Iti Saha
This article presents the cuckoo search algorithm (CSA) for the optimum design of a 4 × 4 dipole planar antenna array (DPAA) taking mutual coupling into account. The CSA is employed to optimise the input parameters such as lengths of each dipole elements and separation distance between the dipole elements of the DPAA in order to achieve higher directivity with low half power beam width and high front to side lobe level with less computational time. The optimal input parameters at 300 MHz are obtained using a multi-objective fitness function. The array is simulated using method of moments codes using MATLAB and verified using MININEC software. Finally, the optimised results are compared with the results of other antenna arrays obtained using several other popular optimisation techniques to evaluate the performance of our proposed DPAA. The optimum design procedure can be used to design similar DPAAs at other operating frequencies in the UHF band.